Fatty acid variation associated with somatic embryogenesis and calli growth of flax (Linum usitatissimum L.) - Cunha, Ana (2002)
Poster apresentado no "13th International Congress of the Federation of European Societies of Plant Physiology (FESPP)" em Creta, Grécia, em 2002.